A STUDY OF ASSERTIVENESS IN A DEBATE SETTING - Yuyun, Ignasia (Indonesian Journal of Applied Linguistics, 2014)
Abstract: This article reports a study on the analysis of assertiveness of students’ argument in a private senior high school debating’s club. This study aims to identify the level of assertiveness of arguments in debating. The study employed mainly a qualitative method focusing on text analysis and involved a debating activity of senior high school students. World School Debating Championship style, Hallidayan’s mood and modality analysis, and the theory of assertiveness in verbal communication became the basis of the analysis. seven phenomena were analyzed in this study including mood type, mood adjunct (conjunctive adjunct), mood metaphor, modality type, modality value, orientation and manifestation of modality, and modality metaphor. This study reveals that the level of assertiveness in argumentation is measured through the total number of declarative mood, conjunctive adjunct, high value of modality, explicit subjective modality, and explicit subjective modality metaphor. The study also shows that the level of assertiveness relatively depends on how the students deliver their arguments. Therefore, the students might need a variety of ways in order to make their argument sound more assertive.  Keywords: argument, assertiveness, debate, mood, mood metaphor, modality, modality metaphor, senior highschool, systemic functional Abstrak: Artikel ini melaporkan sebuah penelitian tentang analisis asertivitas dari argumen siswa yang tergabung dalam kelompok debat di sebuah Sekolah Menengah Atasswasta. Penelitian ini bertujuan untuk mengidentifikasi tingkat asertivitas dari argumen pada kegiatan debat. Penelitian ini menggunakan desain penelitian studi kasus kualitatif yang berfokus pada analisis teks dan melibatkan aktifitas debat siswa Sekolah Menengah Atas. Data diperoleh dari hasil observasi kegiatan debat siswa yang direkam dan dianalisis menggunakan teori debat, teori asertivitas dalam komunikasi verbal, dan analisismood dan modality dari Halliday. Analisis teks tersebut meliputi mood type, mood adjunct (conjunctive adjunct), mood metaphor, modality type, modality value, orientation and manifestation of modality, dan modality metaphor. Hasil temuan penelitian ini menunjukkan bahwa tingkat asertivitas dalam argumentasi diukur dengan jumlah total dari declarative mood, conjunctive adjunct, high value of modality, explicit subjective modality, dan explicit subjective modality metaphor. Penelitian ini juga menunjukkan bahwa tingkat asertivitas dipengaruhi oleh cara siswa menyampaikan argumen dalam berdebat. Oleh karena itu, siswa membutuhkan cara yang beragam untuk membuat argumen mereka lebih asertif. Katakunci: argumen, asertivitas, debat, mood, modalitas,metafora modalitas